Efektivitas Program Tahfidz Al-Qur’an dalam Meningkatkan Hafalan Al-Qur’an di SMA-TQ Muadz bin Jabal Kendari - ST. Resida Yuniar; Nurlathifah Thulfitrah B (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Education is a planned effort aimed at creating an effective learning environment where students can develop their potentials; it seeks to ensure that students become individuals who are confident, competent, independent, and responsible. Introducing students to the Qur'an is one of the ways to increase their faith. Education that includes Qur'an study has a very broad purpose, with its main goal being to influence the individual as a being who obeys their Creator and to reflect this through Islamic values. This study aims to evaluate the Tahfiz Qur'an program at SMA-TQ Mu'adz bin Jabal using the CIPP evaluation model. The research was conducted at SMA-TQ Mu'adz bin Jabal Kendari, using a qualitative descriptive method with the CIPP model (Context, Input, Process, and Product). The reason the author uses the CIPP evaluation model to evaluate the Tahfiz Al-Quran program is because it provides relevance in the decision-making process related to the planning of the program being implemented.The data collection process was conducted using observation and interview techniques. The results of this study show that the Tahfidz Al-Quran program at SMA-TQ Mu'adz bin Jabal Kendari has made real progress or development in every component—context, input, process, and product. These range from human resources supporting the program to facilities that do not create much burden and do not require special funding. However, the collaboration between the school and the parents has not yet been effectively implemented; this is because not every parent is able to track their children’s progress in Quran memorization.